2015
DOI: 10.22430/24223182.122
|View full text |Cite
|
Sign up to set email alerts
|

Análisis del comportamiento bursátil de las principales bolsas financieras en el mundo usando el análisis multivariado (análisis de componentes principales PCA) para el periodo de 2011 a 2014

Abstract: El objetivo de esta investigación es analizar el comportamiento bursátil de 27 bolsas financieras en el mundo, mediante el análisis de componentes principales PCA (por sus siglas en inglés). Esta técnica permite agrupar las variables correlacionadas entre sí separándolas de las que no, obteniendo un nuevo espacio reducido en donde se espera la formación de grupos de bolsas financieras con similitudes en su comportamiento bursátil, facilitando su análisis e interpretación.La metodología para abordar esta invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 1 publication
0
2
0
3
Order By: Relevance
“…In the context of entrepreneurship, behavioral beliefs may be defined as expectations about advantages and disadvantages that accrue when an individual starts a business (Marcati et al, 2008). Among the principal advantages that permit existing strong relations between behavioral beliefs and entrepreneurial attitudes to be expressed are financial independence, greater financial reward, risk taking and the desire to achieve personal and professional goals (Henderson, 2002;Quiroga-Juárez and Villalobos-Escobedo, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In the context of entrepreneurship, behavioral beliefs may be defined as expectations about advantages and disadvantages that accrue when an individual starts a business (Marcati et al, 2008). Among the principal advantages that permit existing strong relations between behavioral beliefs and entrepreneurial attitudes to be expressed are financial independence, greater financial reward, risk taking and the desire to achieve personal and professional goals (Henderson, 2002;Quiroga-Juárez and Villalobos-Escobedo, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the criteria listed for the analysis, it can be observed that social mission is more relevant for ventures of "Replacement of lost services in declining / isolated areas", because their purpose it to try to provide services such as transportation and grocery sales, which can be financially inviable (Quiroga-Juárez and Villalobos-Escobedo, 2015). For that reason, entrepreneurs try to satisfy those needs.…”
Section: Job Creationmentioning
confidence: 99%
“…Pavón y Hidalgo (1997) definen la GTI como un proceso orientado a organizar y dirigir los recursos disponibles, tanto humanos como técnicos y económicos, con el objetivo de aumentar la creación de nuevos conocimientos, generar ideas que permitan obtener nuevos productos, procesos y servicios o mejorar los existentes y transferir esas ideas a las fases de producción y comercialización. En otros términos, la gestión tecnológica se encarga de la generación de conocimiento útil, mientras que la gestión de la innovación le corresponde su aplicación sistemática para producir innovaciones (Pabón & García, 2013;Quiroga-Juárez & Villalobos-Escobedo, 2015;Giraldo-Jaramillo & Montoya-Quintero, 2015).…”
Section: La Gestión De La Tecnología E Innovaciónunclassified